Character values in the handbook Tendances A2: Méthode de Français: An ecolinguistic perspective - Santoso, Bernadus Wahyudi Joko; Hasyim, Mohamad Yusuf Ahmad; Nurjaleka, Lisda; Rochman, Muh. Nur (Jurnal Cakrawala Pendidikan, 2025)
This study examines the integration of conservation character values, as promoted by Universitas Negeri Semarang (UNNES), within the Tendances A2: Méthode de Françaishandbook, using an ecolinguistic framework. UNNES, a conservation-oriented university, upholds values such as creativity, humanism, honesty, and fairness, aiming to instill these principles in its students. Since the Tendances A2 handbook was developed in a French socio-cultural context, this research seeks to assess its alignment with Indonesian conservation values through an ecolinguistic lens, which focuses on the relationship between language, culture, and the environment. The study utilized intensive observation and the Bang and Døør dialog model for descriptive and interpretative analysis. The findings show that all eight conservation character values advocated by UNNES are represented in the handbook, with creativity standing out as the most prominent value, emphasizing the handbook’s potential to encourage innovative thinking. Humanism and honesty were also significant, fostering ethical and empathetic communication. This ecolinguistic approach reveals how the handbook, despite its European context, effectively embodies UNNES’s conservation ethos by reflecting the interconnectedness of language, culture, and environmental values. Consequently, the Tendances A2 handbook is highly recommended for use in French Literature courses at UNNES, as it supports both language learning and the cultivation of essential conservation values.